An Analysis of Students’ English Word Stress Errors Made by the Final Year Students of English Department at Universitas Negeri Padang - Rada Ayu Pareza; Ratmanida Ratmanida (Journal of English Language Teaching, 2019)
The objective of this research was to identify and to analyze the common type of English word stress errors made by the final year students of English Department at Universitas Negeri Padang based on Academic Word List and also to find out the students’ level of error in English word stress. The research subject was K2-2016 class which consisted of 30 students selected by using cluster random sampling technique. The technique of data collection was speaking test. In analyzing the data, the researcher used Speech Analyzer Software. From the result of the test, the researcher found that the common type of stress error that made by the students was misplaced stress (81.8%) from all the errors occured. The mean of students’ level of error in English word stress was 45.9% which categorized as low error level.Key words: Word Stress, Stress Error, Level of Error